The assistance to families with cancer through the Calgary Model: contributions to the teaching of nursing in public health - Claudelí Mistura (Editorial AAR, 2021)
The aim of this study is describing the importance of teaching the Calgary Model in nursing courses, to develop its application in the care of families with cancer in public health. This is a descriptive study of literature review about 10 national and international scientific works. The analysis of the results was performed in a qualitative and descriptive method. It became evidenced the relevance of the insertion of the Calgary Model in teaching, in nursing courses to promote active learning of students about the evaluation and intervention of families with cancer in public health, developing care under the Family Health Strategy. Thus, highlighting the importance of teaching focused on practices since the beginning of academic training so that students can be experiencing the reality.